Text mining analysis of Malaysia’s national image in China Daily - Zhang, Jie; Mohd Azidan Abdul Jabar,; Farhana Muslim Mohd Jalis, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study takes October. 4. 2013, as a temporal dividing point, conducting a comparative analysis of news closely related to Malaysia in China Daily, over the 10 years before and after this date. The qualitative research software Leximancer 5.0 is employed for text mining analysis. The findings reveal that the themes in the news transitioned from relatively dispersed, generalised coverage to a more focused, in-depth exploration of major events and China- Malaysia cooperation. The primary social actors demonstrated minimal change over the 20 years but became increasingly focused. Sentiment analysis shows that reporting on Malaysia has predominantly been positive, with the proportion of positive sentiment showing an upward trend. However, some negative factors were also observed, such as a shift in the portrayal of the 6th Prime Minister of Malaysia, from positive to negative. Notably, although the MH370 incident was reported with a predominantly negative perspective, it did not persist for long. Positive sentiments towards all associated social actors, except Indonesia, have continued to grow, including China, Singapore, Australia, and ASEAN. This study portrays Malaysia as a promising partner in economic growth and development, an important player in regional and global relations, and a stable and enduring strategic ally. By employing an innovative combination of text mining techniques and discourse analysis, the research not only provides empirical evidence of the evolving discourse surrounding Malaysia but also offers methodological insights for applying computational tools in media studies.